Assessments of occupational injuries among Primary Healthcare Workers in Katsina Local Government, Katsina State - Dalhatu, M. H.; Musa, S. I.; Nura A. M.; Abdullahi, A .H.; Usain, A. A. (UMYU Journal of Microbiology Research, 2025)
Study’s Excerpt: